PENGARUH PERSEPSI KEGUNAAN, KEMUDAHAN, DAN KUALITAS LAYANAN PADA MOBILE BANKING BRIMO TERHADAP KEPUASAN NASABAH - Wijatmoko, Nando Azriel Putra; Mirati, R. Elly; Purwaningrum, Endang (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
BRI is one of the state-owned bainks which became the first state-owned bank in 1946. And BRI has mobile banking called BRImo. This research aims to determine the usefulness, convenience and service quality of BRImo services on customer satisfaction in using BRImo. This was done using a questionnaire and the number of respondents was 100 responidents, who were BRImo users in the Jabodetabek area. The analysis method used is multiple linear regression with SPSS 29.0 tools. The results of this research partially show that the usefulness and service quality riesults have a significant influence on BRImo cusitomer saitisfaction. Meanwhile, the convenience variiable has no effect on BRImo customer satisfaction. And, simultaneously the variables of usability, convenieince and serviice quality have a significiant effect on customer satisfaction using BRImo.